Domination Of Body Fat Distribution Based On Percent Of Body Fat In Late Adolescent Male And Female - Anung Putri Ilahika; Taufan Iskandar; Nurul Choviyah Syaifudin; Aulia Choirunnisa (Universitas Muhammadiyah Malang, 2022)
Background: Body composition consisting of body fat and non-fat body mass is an indicator of health profile. One method for assessing body fat mass is to measure body fat percentage. Body fat can be distributed in the trunk and extremities with many influencing factors, including gender. Still, it is not yet known whether body fat distribution will be different in different categories of body fat percentage. Objective: To understand the differences in the dominance of body fat distribution based on body fat percentage in late adolescent male and female. Method: This observational analytic study used a cross-sectional approach involving 40 male and female respondents (UMM Medical Faculty students) selected using purposive sampling. The data taken was in the form of height, mass, BMI and SFT which were then entered into the Jackson, Pallock, and Ward (1980) formula. The data obtained were analyzed using the fisher's test. Result: The Fisher's test results showed a sig value of 0.409 > 0.005. meaning not significant, so there is no relationship between the distribution of body fat with body fat percentage Conclusion: There is no difference in the dominance of body fat distribution based on body fat percentage in late adolescent male and female